Perspectives on the nature of intellectual styles - Sternberg, Robert Jeffrey 1949-; Zhang, Li-fang (New York [etc.] Springer-Verlag, 2009)
This book takes a unique perspective, arguing that the difference in students'performance may be nothing more than differences in intellectual styles of learning or thinking. Intellectual styles simply refer to individualized ways of processing information.This stimulating and provocative text integrates the most recent theories and research on intellectual styles. The internationally acclaimed contributors address cutting-edge, controversial issues in the field that have yet to be resolved, including whether certain intellectual styles are better than others, how creativity affects intellectual style, and whether styles are traits or states.Key Features: Distinguishes intellectual styles from other constructs, such as intellectual capacity or effort levels Situates the field of styles within the larger context of the psychological, educational, and business literatures Provides concrete guidelines for researchers, teachers, and employers to apply the concept of intellectual styles to educational and business settings Researchers, teachers, employers, psychologists, and students will find this book to be a fascinating, engaging read, offering a breadth and depth of insight into the nature of intellectual styles.
Keywords: Aprendizaje, Psicología del; Libros electrónicos